Improving Students’ Listening Comprehension in Foreign Language Classes through Subtitled Videos - Shayeb, Ahmad; Abu-Zahra, Majdi (Journal of English Language Teaching and Applied Linguistics, 2023)
This research sets out to investigate the importance of video subtitling in improving foreign language students’ listening comprehension. The researchers employed a pre-post test to measure the impact of video subtitling on foreign language learners' listening comprehension achievement at the end of each six units used in the experiment. The study was carried out on five groups representing the five Unlock Cambridge levels taught at Birzeit University in Palestine. These levels include A1, A2, B1, B2 and C. Students are placed in these levels in accordance with their results in the  English Placement test. Results of the study clearly show that the remedial (A1) and the intermediate level (A2 and B1) students have significantly improved their listening comprehension after watching the subtitled video. On the other hand, the advanced level (B2) students showed modest progress in their listening comprehension. The last group (C level ) students showed almost no enhancement in their listening comprehension skills.